PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS APLIKASI CANVA TEMA BENDA DI SEKITARKU KELAS III SD - Putri, Riski; Rapita Silalahi, Beta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning Media is a tool that greatly supports the learning process both indoors and outdoors. This study aims to determine the development of animated video media based on the Canva application with the theme of objects around me for grade III of elementary school. The method used is R&D (Research and Development) or in Indonesian it means research and development. The test subjects in this study were material experts, media experts, and grade III students of Mbernut State Elementary School, totaling 14 students. The research instrument is a measuring tool such as tests, questionnaires, interview guidelines, and observation guidelines used by researchers to collect data in a study. Based on the results of the evaluation conducted on the video learning media assisted by the Canva application, it can be concluded that this media has received a very good assessment from three different validator groups, namely material experts, media experts, and teachers as end users. The evaluation includes aspects of suitability, effectiveness, and quality of the media in supporting the learning process in the educational environment Based on the results of the validity of the validation of material and media experts carried out First, the Validation of Material Experts gave a very positive assessment with a percentage of 95.7%. This indicates that content experts rated the material presented in the video as highly appropriate, aligned with the established curriculum and learning objectives. Criteria such as accuracy, depth of content, and relevance to core competencies were highly rated in this evaluation. Second, Media Expert Validation yielded a score of 85.2%.